Efektivitas Konseling Behavioral Teknik Operant Conditioning dan Self-Management dalam Peningkatan Motivasi Belajar Santri PP. Al-Munawwir Yogyakarta - Sholihaturrahmaniah, Isna; Nurasyikin, Nurasyikin (Green Publisher Indonesia, 2025)
This study aims to test the effectiveness of behavioral group counseling combined with operant conditioning and self-management techniques in increasing learning motivation in PP students. Al-Munawwir. This type of research is experimental research. The purposive sampling method was used to determine the research sample. A total of 40 students from classes 1A and 1B were divided into two groups, 20 students from class 1A as an experimental group, and 20 students from class 1B as a control group. The one-way ANOVA test is used for the average testing of pretest and posttest score data. Data was collected using 20 items on the Learning Motivation Scale. The data can be seen in the results of the average pre-test difference of 59.60 and the results of the average post-test difference which amounted to 71.95. Therefore, the conclusion is stated that behavioral group counseling using operan conditioning and self-management techniques is effective in increasing the learning motivation of students at the Al-Munawwir Krapyak Islamic Boarding School.